Design and Construction of Fluorescent Cellulose Nanocrystals for Biomedical Applications. Issue 11 (6th February 2022) - Li, Ruyi; Liu, Yuqian; Seidi, Farzad; Deng, Chao; Liang, Fangyuan; Xiao, Huining
Abstract: Cellulose nanocrystals (CNCs) are featured with low toxicity, non‐trivial biocompatibility, and cell membrane penetration capability, which allow the constructions of nanoplatforms for biosensing and in vivo imaging. Interfacing CNCs and fluorescent materials into sensors/probes is thus highly topical and has received tremendous interest. This review covers the development of CNC extraction methods and, in particular, their impacts on the surficial properties of CNCs. Whereafter, recently reported strategies for fluorescent functionalizations of CNCs are summarized based on chemical modification, physical adsorption, or in situ growth. Choosing the most suitable strategy, according to the properties of both CNCs and fluorophores, for constructing fluorescent CNCs is also emphasized. With regard to applications of the fluorescent CNCs, this work focuses on the studies which have involved but not been limited to metal ion sensing, physiological pH detection, cell imaging, and tumor antiproliferation. Being aware of the highly flexible construction, appealing structural/optical properties, and outstanding performances in analysis/imaging, it is believed that CNCs are bound to be increasingly investigated in the future and widely applied in the biomedical area. Abstract : This review describes the current state of research and the emerging technologies in the development of fluorescent cellulose nanocrystals (CNCs). Firstly, the CNC preparation methods are summarized and compared. According to the surficial properties of CNCs from different extraction methods, fluorescent functionalizations of CNCs are reviewed in detail, as well as the biomedical applications of the constructed fluorescent CNCs.